Multiplexed and tunable transcriptional activation by promoter insertion using nuclease-assisted vector integration. Issue 12 (1st April 2019) - Brown, Alexander; Winter, Jackson; Gapinske, Michael; Tague, Nathan; Woods, Wendy S; Perez-Pinera, Pablo
Abstract: The ability to selectively regulate expression of any target gene within a genome provides a means to address a variety of diseases and disorders. While artificial transcription factors are emerging as powerful tools for gene activation within a natural chromosomal context, current generations often exhibit relatively weak, variable, or unpredictable activity across targets. To address these limitations, we developed a novel system for gene activation, which bypasses native promoters to achieve unprecedented levels of transcriptional upregulation by integrating synthetic promoters at target sites. This gene activation system is multiplexable and easily tuned for precise control of expression levels. Importantly, since promoter vector integration requires just one variable sgRNA to target each gene of interest, this procedure can be implemented with minimal cloning. Collectively, these results demonstrate a novel system for gene activation with wide adaptability for studies of transcriptional regulation and cell line engineering.